PERANCANGAN KAMPANYE SOSIAL ‘LANTANGKAN’ SEBAGAI UPAYA MELAWAN PELECEHAN SEKSUAL VERBAL - Liliandari, Annisa Rizka; Hindraruminggar, Rika (Anggada : Jurnal Desain dan Seni, 2022)
Sexual Harassment is one of the form of the sexual assault that we faced in Indonesia, where the number of cases according to the National Commission of Violence Againts Woman has reached 431,471 cases back in 2019. The lack of information which can helps to grow the public awareness about the phenomenon of sexual harassment is also a major factor of those cases. Based on the Center for Strategic and International Studies, it is stated that teenagers, especially millennials in Indonesia prefer to watch television or other video platform and media in the process of receiving information. In responding to the phenomenon of the lack of awareness of verbal-sexual harassment, the author designed a campaign using the audio visual media and sinematographic techniques which can provide more information with images, text, sound and videos. In the process of designing the social campaign, the author also designs a supporting media such as informative content using social media platforms and printable media that can be used in the daily activities to increase public awareness to fight verbal sexual harassment.